O exercício físiico induz ajustes termorregulatorios ecardiovasculares que sao mediados pela neurotransmissãocolinérgica dos nucleos ventromediais hipotalâmicos - Samuel Penna Wanner (2006)
The aim of this study was to evaluate the participation of cholinergic muscarinic receptors in the ventromedial hypothalamic nuclei (VMH) on heat balance, cardiovascular adjustments and central fatigue during treadmill exercise (24 m.min-1, 5% inclination). Rats were submittedto two experimental situations separated by an interval of at least two days. Tail skin temperature, core body temperature (Tb) and arterial pressure were measured after the injection of 200 L of 2,5 x 10-2 M methylatropine (Atr) or 0.15 M NaCl solution (Sal) into the VMH. Atr injection into the VMH amplified the exercise-induced increase in Tb andresulted in a delay in the rise of skin temperature. The increased heat storage needed to trigger the heat loss mechanisms observed in VMH Atr-treated rats may be responsible for the 37% decrease in the performance of these animals (21.0 ± 2.9 min Atr vs. 33.5 ± 3.4 minSal; n = 8; p 0.001). Cholinergic blockade of VMH has also acelerated the blood pressure adjustments (mean arterial pressure maximal value: 132.6 ± 3.9 mmHg at 3 min Atr vs. 125.2±4.1 mmHg at 9 min Sal; n = 7), which were related to the percentage of total exercise time. We conclude that cholinergic muscarinic receptors in the VMH modulate sympatheticactivation and facilitate heat loss during exercise. Furthermore, these adjustments induced by intra-ventromedial cholinergic neurotransmission determine exercise time until fatigue.